LSVT as a fundamental therapeutic technique for improving voice in parkinsonism: Evidence from three cases - Nayana Narayanan; Zaba N. Rahman (Annals of Movement Disorders)
Lee Silverman Voice Treatment (LSVT) is one of the main treatments proposed for improving the loudness of hypokinetic dysarthria clients. It follows the modus operandi of training the client to achieve maximum loudness of voice with the highest effort and calibrating the voice at that level. It is very important to pool the evidence obtained from the patients to understand the effectiveness of the technique. My study aims to collect evidence of LSVT treatment from three patients with various stages and severities of Parkinsonism. Results reveal that the loudness level has significantly increased after LSVT treatment in comparison to pre-therapy levels. The percentage of shimmer value has decreased post-therapy. From the result, it is evident that LSVT was highly successful in elevating the loudness of all three clients. The reduction in shimmer percentage coincided with an improved overall quality of voice. Hence, we can conclude that LSVT is an apt treatment method for improving loudness in hypokinetic dysarthria clients.